INFLUENCE OF THE STATE CREDITING IS ON PROMISSORY STRENGTH OF UKRAINE SECURITY - O. Cheberyako (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
In the article is grounded necessity of realization of the state crediting for coverage of deficit of the state budget on the modern stage, the modern state of national debt of Ukraine is investigated and the analysis of basic indicators of promissory safety of Ukraine comes true. During the last years a tendency is traced to the increase of national debt of Ukraine, that it is related to the high currency risks of external debt, by an unstable situation with refunding of debts of previous years, and also pressure of promissory payments on public finances. Without regard to that the level of national debt of Ukraine as yet remains within the limits of maximum value, the analysis of promissory situation testifies to the threatening tendency of decline of promissory strength of Ukraine security as a result of the protracted borrowed financing of economy, increase of national debt in relation to GDP, sharp increase of the promissory loading on the state budget and realization of the new borrowing related to the difficult political, economic and military situation.